(untitled) - Turvey, Brent E. (Amsterdam, 2017)
This book introduce forensic investigations: a primer. Law and evidence, Investigative ethics. Investigators and the scientific method. Crime scene investigation and analysis. Crime scene processing. Forensic victimology. The sexual assault examination. Medicolegal death investigation: protocols and practice. Forensic interviews. The polygraph: uses and misuses. Investigating allegations of police torture: forensic protocols and psychological assessment. Forensic investigations for court: probation, sentencing, mitigation issues in capital cases
Keywords: Khoa học pháp y,Forensic sciences